PEMANFAATAN APLIKASI ‘CHAO’S (CHAT ONLINE PADA SMARTPHONE) SEBAGAI MEDIA PEMBELAJARAN DALAM MEMFASILITASI BELAJAR MANDIRI UNTUK MENINGKATKAN HASIL BELAJAR - Muhammad Hifdil Islam; Farich Purwantoro (UNZAH Genggong, 2020)
This study aims to determine the effect of the use of Media CHAOS (Chat Online on Smartphone) to the self- directed learning students and determine the effect of student learning outcomes through self- directed learning with the use of the media CHAOS (Chat Online on Smartphone) in class X MA and SMA Mazra'atul Ulum Paciran , In this study, researchers used a quantitative approach with quasi experimental design methods to the study design using non equivalent control group design. The study involved two homogeneous classes, each class comes from a different school. The first school used as the experimental group and the second school used as a control group. In this study, the pattern of use of the media refers to the stages of the development model ASSURE which consists of six steps, namely: 1) Analyze learners, 2) State objectives, 3) Select or modify media, 4) Utilize technology, media and materilas, 5) Require learner response, and 6) Evaluate and Revise. Media used in CHAOS (Chat Online on Smartphone) is WA(WhatsApp). CHAOS utilization process in this research is done by using the media as a group chat that used students as subjects of media discussions subjects physics of motion in the process of self- directed learning, self-directed learning and then the good results will also affect student learning. The data was obtained as follows: 1) The effect of the use of media to learn independently obtained CHAOS is greater than t tabe that is 23.250> 1.992; (df) 77, with a significance level of less than 0.05 is 0.000. 2) The effect of self-learning using the learning outcomes obtained CHAOS learning outcomes (pretest) note that the value tcount> ttable(0.945> 1.992). And the value of significance (0.347> 0.05). The learning result (posttest) note that the value tcount> ttable (14.026> 1.992). And the significance value (0.000> 0.05). Based on analysis of these data, it can be concluded that the application CHAOS significantly influence independent learning, and independent study using CHAOS significantly influence learning outcomes. Keywords: Application CHAOS, Self-directed Learning, Learning Outcomes